Relationship Between Selected Performance Tests and Non-contact Sports Injuries in Male Wushu Players - Ghafouri, Abbas; Mohammadi, Fariba; Ganji, Behnaz (Physical treatments, 2020)
Purpose: Several tests have been proposed as injury predictor inventories in various sports; however, it is important to recognize which test is more appropriate to predict the injuries of a particular sport. Therefore, the present study aimed to investigate the relationship between selected functional tests and lower limb injuries in elite male wushu athletes. Methods: In total, 40 wushu player were recruited from the national league (Mean±SD age: 25.1±4.9 y, weight: 67.3±7.7 kg, height: 175.3±4.7 cm). Functional Movement Screening (FMS), Tuck jump, single and double leg squats, Star Excursion Balance Test (SEBT), and Stork balance tests were performed in this research. All of the study variables were measured before the national competition, and after the competition, the rate of the injuries were assessed. The correlation between them was evaluated, subsequently. Descriptive data were used to describe the collected results. Besides, multivariate linear regression analysis was used to explore the relationship between the study variables. Results: Multivariate linear regression analysis data suggested that LESS, stroke balance test, single-leg squat, and SEBT failed to predict lower extremities injuries; however, Tuck jump, FMS, and double leg squat could predict lower extremities injuries. Conclusion: Based on the collected results, among the studied tests, trainers and researchers are suggested to employ the Tuck jump, FMS, and double leg squat tests to predict injuries in wushu male players; this test can also be used to prevent injuries in players.